Laser Measurement Technology Fundamentals and Applications - Donges, Axel; Noll, Reinhard (Springer Series in Optical Sciences, 2015)
Laser measurement technology has evolved in the last years in a versatile and reflationary way. Today, its methods are indispensable for research and development activities as well as for production technology. Every physicist and engineer should therefore gain a working knowledge of laser measurement technology. This book closes the gap of existing textbooks. It introduces in a comprehensible presentation laser measurement technology in all its aspects. Numerous figures, graphs and tables allow for a fast access into the matter. In the first part of the book the important physical and optical basics are described being necessary to understand laser measurement technology. In the second part technically significant measuring methods are explained and application examples are presented. Target groups of this textbook are students of natural and engineering sciences as well as working physicists and engineers, who are interested to make themselves familiar with laser measurement technology and its fascinating potentials.